The Adoption Of Digital Technology By Subcontracting Manufacturing Companies In Algeria - Dermechi, Feriel; Zakane, Ahmed (جامعة الوادي University of Eloued, 2025)
This study examines the adoption of digital technologies by subcontracting manufacturing companies in Algeria, focusing on associated issues, benefits, and challenges. A random sample of 102 companies was surveyed using an online structured questionnaire covering company characteristics, digital technology use, and performance indicators. The results indicate that most subcontracting manufacturing companies gradually integrate digital technologies, such as e-commerce platforms and supply chain management systems. This adoption enhances operational efficiency, optimises resource management, and reduces production costs. However, certain challenges remain, particularly the high initial investment costs and the lack of digital skills among employees, which slow down their full integration into production and management processes.
مقال
Keywords: digital technologies; subcontracting manufacturing companies; Algeria; questionnaire